PENGARUH PENERAPAN MODEL PEMBELAJARAN EVERYONE IS A TEACHER HERE TERHADAP MOTIVASI BELAJAR SISWA KELAS VIII SMPN 4 SINGINGI HILIR KABUPATEN KUANTAN SINGINGI - Diana, Eva Ria; Gimin, Gimin; Haryono, Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The research aims to increase student learning motivation by means of impelentation of everyone is a teacher here model to motivation learning of VIII class SMP N 4 singingi hilir kabupaten kuantan singingi. The research was a kind of experiment. Research conducted at SMPN 4 singingi hilir kabupaten kuantan singingi. Samples from this study are students of class VIII2 as an experimental class and the students in class VIII4 as the control class, this sample was randomly selected after tests of homogeneity in all populations. Classes are classes given experimental treatment using Generative Learning learning model, while the control class is the class that was treated using the usual method implementation discussion. Based on the results of hypothesis testing data analysis obtained t> t table ie 27,93>2,021, his shows the differences in learning motivation of students that learning PPKn before and after bonds with and without the use of learning model everyone is a teacher here in class VIII SMPN 4 Singingi hilir Kabupaten singingi hilir. Thus the hypothesos which reads that is an affect of using everyone is a teacher here learning toward students’ learning motivation class VIII at SMPN 4 singingi hilir kabupaten kuantan singingi, can be accepted.Keyword : Everyone Is A Teacher Here, Learning Motivation